Insights into Standard Precaution Knowledge and Adherence among Healthcare Workers: Evidence from Tertiary Care Hospitals in Peshawar, Pakistan : Standard Precautions and Healthcare Workers - Zahir, Salman; Khan, Khansa; Sardar, Noor; Jahan, Sarwat; Ali, Muhammad Mehr; Khan, Aamir; Khattak, Janeeta; Mazhar, Somia; Shah, Jamal (Pakistan Journal of Health Sciences, 2024)
Healthcare workers (HCWs) are at risk of being exposed to blood-borne infections when performing clinical activities, hence conventional measures must be followed. The study conducted in Peshawar was motivated by the inadequate adherence to standards in Pakistan. Objective: To evaluate tertiary care hospitals' healthcare workers' (HCWs) awareness of and adherence to standard precautions. Methods: Over the course of six months, 421 HCWs employed in a variety of public and commercial tertiary healthcare settings in Peshawar, Pakistan, participated in cross-sectional research. Convenient sampling was employed in the selection of participants. Three portions of a standardized questionnaire addressing adherence, knowledge, and demographics were administered. For data analysis SPSS version 27® was used, evaluating adherence and knowledge using scoring methods. Results: The majority of participants (78.1%) were new in their areas, and 68.2% had completed standard precautions training. Although the majority of healthcare workers (HCWs) showed high understanding (67.46%), there were still significant gaps in their knowledge, especially when it came to false beliefs about HIV and Hepatitis patient care. However, there was excellent adherence, particularly for trash disposal (73.6%) and hand hygiene (91.4%). When it came to knowledge and adherence, doctors outperformed lab technicians and nurses. Conclusions: Despite knowledge limitations, healthcare workers (HCWs) in Peshawar displayed outstanding adherence to basic procedures, going beyond theoretical comprehension. This underscores the importance of practical implementation in healthcare settings.